Project on Strengthening the Profile of Pancasila Students : Implementation, Role of Teachers, and Student Character - Waruwu, Ermina; Sinulingga, Aldi Alfrianza; Sitepu, Abdi Guna; Sugiyana, F. X. (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to analyze the project of Strengthening the Profile of Pancasila Students (P5), the role of teachers in improving P5, and the characters developed in P5 implemented by PPG-STPKat students of St. Francis Asisi Semarang. The mixed method research design was used. The probability sampling technique was used to select 14 schools for the research population. Quantitative data was collected through questionnaires assessing the implementation of the P5 project and the role of teachers and analyzed using ANOVA Linearity, Linear Regression, and the F Test. Interviews were used to collect qualitative data, which was then analyzed using data reduction, data presentation, and conclusion drawing. The results showed that the simultaneous implementation of the P5 project and the role of the teacher had a high effect on student character building (99.1%). The linearity test revealed a linear relationship between P5 project implementation and learner character, with a significance value (p) of 0.000 0.05. P5 has been implemented in elementary schools, and teachers serve as role models, motivators, inspirers, and evaluators, according to qualitative findings. Students’ Pancasila character profile depicts a character of faith, piety to God Almighty, and noble character. Positive aspects of mutual cooperation included improved collaboration skills and various aspects of mutual cooperation. This study’s recommendations include increasing the number of meeting hours, involving a team of facilitators, and ensuring school readiness. Students must be encouraged to participate actively in the P5 project and to develop the Pancasila learner profile attitude.